Peran Manajemen Sekolah Dalam Penerapan Common Asean Tourism Curriculum Di Smk Negeri 3 Malang - Andrean Hartanu Wibowo; Henny Suharyati; Rais Hidayat (JURNAL MANAJEMEN PENDIDIKAN, 2023)
THE ROLE OF SCHOOL MANAGEMENT IN THE IMPLEMENTATION OF THE COMMON ASEAN TOURISM CURRICULUM AT SMK NEGERI 3 MALANGTourism Vocational School is one of the concepts in vocational education, where students are taught the attitudes, knowledge, and skills needed by the Tourism Industry at both national and international levels. For example, a school that applies the concept of a tourism vocational school is SMK Negeri 3 Malang, which integrates two curricula consisting of the 2013 curriculum and the CATC. This study aims to examine and describe the uniqueness of the processes and stages in school management at SMK Negeri 3 Malang, which is located in Malang-East Java, in developing CATC at the SMK level. The school management study included the stages of planning, organizing, directing, and implementing, as well as controlling. This study uses a qualitative method, with the researcher as the instrument. Data collection techniques used are interviews, observations, and documentation studies. Based on the existing data and information, the results were obtained, and it can be concluded that a good and structured process of planning, organizing, directing, and controlling is the main supporting factor in developing the curriculum for school operational units at SMK Negeri 3 Malang. To be able to achieve the objectives as stated in the curriculum of the school's operational unit, detailed planning, organization according to needs, direction, and implementation in accordance with programs that have been prepared and planned, as well as intensive control on a regular basis with instruments that are prepared objectively and measurably is needed.